Direct measurements of 3d structure, chemistry and mass density during the induction period of C3s hydration. (November 2016) - Hu, Qinang; Aboustait, Mohammed; Kim, Taehwan; Ley, M. Tyler; Bullard, Jeffrey W.; Scherer, George; Hanan, Jay C.; Rose, Volker; Winarski, Robert; Gelb, Jeffrey
Abstract: The reasons for the start and end of the induction period of cement hydration remain a topic of controversy. One long-standing hypothesis is that a thin metastable hydrate forming on the surface of cement grains significantly reduces the particle dissolution rate; the eventual disappearance of this layer re-establishes higher dissolution rates at the beginning of the acceleration period. However, the importance, or even the existence, of this metastable layer has been questioned because it cannot be directly detected in most experiments. In this work, a combined analysis using nano-tomography and nano-X-ray fluorescence makes the direct imaging of early hydration products possible. These novel X-ray imaging techniques provide quantitative measurements of 3D structure, chemical composition, and mass density of the hydration products during the induction period. This work does not observe a low density product on the surface of the particle, but does provide insights into the formation of etch pits and the subsequent hydration products that fill them.